Studi Kualitas Silika Menggunakan Metode Geokimia Daerah Tahi Ite Kabupaten Bombana, Provinsi Sulawesi Tenggara: Silica Quality Study Using Geochemical Method in Tahi Ite Area, Bombana Regency, Southeast Sulawesi Province - Almarabi, Laode Muhammad Imaduddin; Bakri, Hasbi; Thamsi, Alam Budiman (Journal of Engineering Science and Technology Applications, 2025)
Silica is a rock weathering mining material containing the main mineral, silica (SiO2). Quartz sand is widely used in Indonesia, such as in the glass industry, cement industry, refractory bricks, and as a furnace coolant. The purpose of the study was to determine the carrier minerals of quartz sand and associated minerals in the Tahi ite area of ​​Bombana Regency, to determine the geochemical composition of quartz sand, and to determine the quality of quartz sand based on the Indonesian National Standard (SNI). The location of this study is in Southeast Sulawesi Province, Bombana Regency. This research method uses XRD (X-ray diffraction) analysis and XRF (X-ray fluorescence) analysis which has Quartz (SiO2), Calcite (CaO3), Muscovite (Al3HKO12Si3), Kaolinite (Al2H4O9Si2), Albite (AlNaO8Si3), Chabazite (CaK2Na2Mg). Silica deposits have elements (SiO2) 46.50% and Aluminum Oxide compounds (Al2O3) 24.33% and have larger elements (SiO2) 58.28% and Aluminum Oxide compounds (Al2O3) 25.80%.